PASSIVE ACQUISITION OF PRESCHOOL CHILDREN IN SUNDANESE LANGUAGE - Fitriyani, Risa (Syntax Literate, 2019)
In linguistic and acquisition theory, passive is a complex structure which is notacquired in child language. This construction is a late acquisition for about fourthage in English, the age of fifth in German and eighth in Hebrew. In Sundaneselanguage as one of language in Indonesia, passive structure was acquired and usedproductively earlier in an almost perfect construction of the age of three. Data inthis research showed that the child of 3,1 years old; 4,1 years old; 4,7 years old;and 5,0 years old which are used Sundanese language as their first language, canproduce passive constructions of the simple to the complex ones although there arestill many errors in the order of the constructions. Through analysis of 75 passivesentence as the data, this research described for three points in the statement ofresearch. Those are what the semantic roles which are include in the passiveconstruction are, how the stages of the passive production of the partisipants are,and what the similarities and differences between boys and girls in the productivityof passive constructions are. The result of reasearch showed that children acquiredpassive construction from the simple one based on the structure and meaning tothe more complex one. The stages are from the use of first passive’s first class inSundanese grammar of Coolsma (1985). For the similarities and differencesbetween boys and girls are that all children took the same stages of the passiveproduction either in semantic roles or verb class of passive but the girls tend to bemore verbalistic than boys. This was showed by the number of data and theaccuracy of their constructions. Boys are tend to say by the simple construction andusing the gesture. .Keywords: Passive structure, Sundanese Language, Semantic Role, the Stages of Language Acquisition